Study of the water-gas shift reaction over Pt supported on CeO 2-ZrO2 mixed oxides - Vignatti, Charito Ivana (2011)
The water gas shift (WGS) reaction was studied on Pt/CeO2, Pt/ZrO2 and Pt/CexZr1-xO2 catalysts. All the samples were characterized by a variety of physical and spectroscopic techniques. The catalyst activities were evaluated at 250 °C in a recirculating reactor through CO conversion versus time tests and also by in situ diffuse reflection infrared Fourier transform spectroscopy (DRIFTS). The sample activity for the WGS reaction depended on chemical composition. Pt/CexZr1-xO2 catalysts with x ≥ 0.5 were more active than Pt/CeO2, probably because the addition of Zr to ceria increased both the surface area and the reducibility of ceria. The lowest CO conversion rates were obtained on Pt/ZrO2 and Zr-rich Pt/Ce xZr1-xO2 samples. Based on DRIFTS experiments, this result was interpreted by considering that in the WGS formate associative mechanism the stability of formate species is higher on Zr-rich supports.